Pengembangan E-Modul Pada Mata Kuliah Sanitasi Hygiene dan K3 Prodi Tata Boga - Putri, Yuzia Eka; Akmal, Nikmat; Elfita, Arzulliah; Yupelmi, Mimi; Ambiyar, Ambiyar; Jalinus, Nizwardi; Putra, Firmansyah (Universitas Negeri Padang, 2023)
This study aims to develop teaching materials in the form of e-modules so that student learning outcomes increase in Sanitation Hygiene and K3 courses. The research method used is the fourd-D method. The research was conducted at the Culinary Study Program, Medan State University. The results of the validity test with the media validator obtained a value of 0.79 in the high category, the results of the module content validity test obtained a value of 0.76 in the high category and for the results of the language validity test it obtained a validity value of 0.82 in the very high category. In general, the results of the module validity test are declared valid and can be tested on students as users. Furthermore, the practicality test of the module through the practicality test of student responses obtained a score of 80.68 in the practical category, and the practicality test of the lecturer's response obtained a practicality value of 78.86% in the practical category. If an average score is obtained of 78.30% in the practical category, it means that the developed module is seen from the ease of use, the attractiveness of the presentation and the practical benefits used by students. For the effectiveness test, a gain score of 0.635 is obtained in the moderate category. The conclusion of the test results is the use of the Sanitation Hygiene and K3 module which was developed to be used effectively to support lectures and greatly contribute to the development of scientific knowledge in the culinary field.